Drain vs. no-drain for acetabular fractures after treatment via a modified stoppa approach: A retrospective study - Jin, Lin; Wang, Zhongzheng; Zhao, Kuo; Lian, Xiaodong; Chen, Wei; Zhang, Yingze; Hou, Zhiyong (Frontiers in Surgery, 2023)
Objective. The aim of this study was to compare the clinical efficacy of close suction drainage (CSD) and no-CSD after a modified Stoppa approach for surgical fixation of acetabular fractures. Methods. This retrospective study included 49 consecutive acetabular fracture patients who presented to a single level Ⅰ trauma center for surgical fixation using a modified Stoppa approach from January 2018 to January 2021. All surgeries were performed by a senior surgeon using the same approach, and the patients were divide into two groups based on whether CSD was used after the operation. Details of the patient demographics, fracture characteristics, intraoperative indicators, reduction quality, intra- and postoperative blood transfusion, clinical outcomes and incision-related complications were collected. Results. No significant differences were found in the demographics, fracture characteristics, intraoperative indicators, reduction quality, clinical outcomes and incision-related complications between the two groups (P>0.05). The use of CSD was associated with a significantly higher postoperative blood transfusion volume (P=0.034) and postoperative blood transfusion rate (P=0.027). In addition, there was a significant difference in postoperative temperatures especially on postoperative Day 2 (no-CSD 36.97 ± 0.51 ℃ vs. CSD 37.34 ± 0.69 ℃, P=0.035), and higher visual analogue scale (VAS) scores, especially on postoperative Day 1 (no-CSD 3.00 ± 0.93 vs. CSD 4.14 ± 1.43, P=0.002) and 3 (no-CSD 1.73 ± 0.94 vs. CSD 2.48 ± 1.08, P=0.013). Conclusion. The results of this study suggested that routine use of CSD was not recommended for patients with acetabular fractures after surgical fixation using a modified Stoppa approach.